An Extremely Rare Complication: Abdominal Aortic Aneurysm Rupture Caused by Migration of a Zenith Main Body Years After Repair of the Suprarenal Stent Separation. (April 2019) - Ueda, Tatsuo; Tajima, Hiroyuki; Murata, Satoru; Iwata, Kotomi; Saitou, Hidemasa; Miki, Izumi; Yasui, Daisuke; Sugihara, Fumie; Onozawa, Shiro; Morota, Tetsuro; Kumita, Shin-ichiro
Purpose: To report an unusual case of an abdominal aortic aneurysm (AAA) rupture caused by migration of a Zenith stent-graft main body years after its separation from the suprarenal stent.Case Report: A 72-year-old man underwent endovascular aneurysm repair with a Zenith stent-graft for an infrarenal AAA in year 2000. At that time, a femorofemoral bypass was performed because the left external iliac and common femoral arteries were dissected during treatment. In 2013, follow-up computed tomography (CT) showed disconnection of the uncovered proximal stent, which led to a type Ia endoleak. An additional Zenith main body and Large Palmaz XL balloon-expandable stent were deployed; the endoleak disappeared. In 2016, the patient had abdominal pain, and emergency CT showed AAA rupture caused by migration of the first main body deployed in 2000 under the distal edge of the contralateral (left) leg of the additional main body from 2013, which led to a type IIIa endoleak between the 2 main bodies. A converter and iliac legs were deployed to successfully seal the type IIIa endoleak. The patient remains well 18 months after the second repair; CT scans document stable stent-grafts and no endoleak.Conclusion: Physicians should be aware of the potential risk for AAA rupture caused by late main body migration after treatment for suprarenal stent separation from a Zenith stent-graft.